Education policy and employability: What are the most influential competencies? - Freire Seoane, María Jesús; Teijeiro Alvarez, Mercedes; Pais Montes, Carlos (Education Policy Analysis Archives, 2011)
This paper analyzes the generic professional skills most valued by employers and university graduates. This research is a qualitative and quantitative study that uses data from two main sources: graduates of the University of La Coruña and employers of this province. The analysis herein, applies the Logit model, and it empirically contrasts the influence of certain variables related with skills on the probability of being employed. The results underpin the opinion stated by experts; currently the most highly regarded skills in the labour market are those that belong to the systematic type, therefore, personal and non-transferable, in detriment of instrumental skills closer related with graduates’ capacity and education.